Uso de un sistema de información en la gestión del proceso de estacionamiento vehicular en un hospital público peruano. - Vásquez-Romero, E.J. (2023)
The main objective of this research is to evaluate the effect of the use of an information system in the management of the vehicle parking process in a public hospital in Lima, where all activities in this regard are manually carried out by workers, which causes times of Wait, hinder vehicle flow, cause discomfort to people who visit the hospital and create deficits in the administration. Therefore, an information system was designed and implemented using the RUP methodology, consisting of four phases: conception, elaboration, construction and transition. Workflows were developed, including business modeling, requirements, analysis and design, implementation, tests and deployment. The modules developed with open source technologies were: processes, administration, security and reports. As a result, it was obtained that the use of the information system positively impacted the vehicle management process by reducing the time to carry out parking activities by 66.67%, the worker's satisfaction increased by 34.33%, It also increased the reliability of the calculation of parking fees by 96% and 52% of the activities of the process were automated, optimizing the use of resources.